Comparative analysis of SARS-CoV-2 variants Alpha (B.1.1.7), Gamma (P.1), Zeta (P.2) and Delta (B.1.617.2) in Vero-E6 cells: ultrastructural characterization of cytopathology and replication kinetics - Debora Ferreira Barreto Vieira; Derick Mendes Bandeira; Marcos Alexandre Nunes da Silva; Ana Luisa Teixeira de Almeida; Mia Araújo; Ana Beatriz Machado; Luis Fernando Lopez Tort; Valéria Pereira Nacife; Marilda M. Siqueira; Fernando Couto Motta; Alex Pauvolid-Corrêa; Ortrud Monika Barth (Brazilian Journal of Infectious Diseases, 2024)
This study compares the effects of virus-cell interactions among SARS-CoV-2 variants of concern (VOCs) isolated in Brazil in 2021, hypothesizing a correlation between cellular alterations and mortality and between viral load and transmissibility. For this purpose, reference isolates of Alpha, Gamma, Zeta, and Delta variants were inoculated into monolayers of Vero-E6 cells. Viral RNA was quantified in cell supernatants by RT‒PCR, and infected cells were analyzed by Transmission Electron Microscopy (TEM) for qualitative and quantitative evaluation of cellular changes 24, 48, and 72 hours postinfection (hpi). Ultrastructural analyses showed that all variants of SARS-CoV-2 altered the structure and function of mitochondria, nucleus, and rough endoplasmic reticulum of cells. Monolayers infected with the Delta variant showed the highest number of modified cells and the greatest statistically significant differences compared to those of other variants. Viral particles were observed in the cytosol and the cell membrane in 100 % of the cells at 48 hpi. Alpha showed the highest mean particle diameter (79 nm), and Gamma and Delta were the smallest (75 nm). Alpha and Gamma had the highest particle frequency per field at 48 hpi, while the same was observed for Zeta and Delta at 72 hpi and 24 hpi, respectively. The cycle threshold of viral RNA varied among the target protein, VOC, and time of infection. The findings presented here demonstrate that all four VOCs evaluated caused ultrastructural changes in Vero-E6 cells, which were more prominent when infection occured with the Delta variant.